Fetal alcohol spectrum disorder prevention program: SBIRT's role in averting fetal alcohol spectrum disorders. Issue 12 (23rd July 2019) - Manriquez, Maria; Starer, Jacqueline; Parisi, Vanessa; Tracy, Erin; McFadden, Tonya; Penney, Lily
Abstract: Empowering obstetricians to assess and improve their own practices of screening brief intervention and referral to treatment (SBIRT) in treating alcohol use disorders (AUDs) and preventing fetal alcohol spectrum disorder (FASD) is the goal of the American College of Obstetricians and Gynecologist (ACOG) FASD Prevention Program. The FASD Prevention Program is a CDC funded initiative of the ACOG which is the largest specialty professional membership organization in the United States. Obstetrics and gynecology as a specialty is dedicated to the broad, integrated medical and surgical care of women's health throughout their lifespan. Understanding of reproductive physiology, including the physiologic, social, cultural, environmental, and genetic factors that influence disease in women, is a major priority for ACOG. Preventive counseling and health education are essential and integral parts of the practice of obstetricians and gynecologists as they advance the individual and community‐based health of women of all ages. The FASD Prevention Program aims to provide obstetrician‐gynecologists with the resources and tools needed to communicate with patients and the communities they serve about alcohol use during pregnancy. This review describes activities to empower and educate providers to address alcohol use disorder in pregnancy and the effect of FASD.